2021
DOI: 10.3389/fimmu.2021.807600
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CLEC2-Podoplanin Axis as a Promising Target for Oral Cancer Treatment

Abstract: Cancer tissues are not just simple masses of malignant cells, but rather complex and heterogeneous collections of cellular and even non-cellular components, such as endothelial cells, stromal cells, immune cells, and collagens, referred to as tumor microenvironment (TME). These multiple players in the TME develop dynamic interactions with each other, which determines the characteristics of the tumor. Platelets are the smallest cells in the bloodstream and primarily regulate blood coagulation and hemostasis. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 201 publications
(232 reference statements)
0
20
0
Order By: Relevance
“…Platelets mainly regulate blood coagulation and hemostasis. The asymmetric status of platelets contributes to cancer promotion and progression, directly causing thrombocytosis in patients with cancer [ 55 ]. Present cell research has already indicated that platelets enhance the invasion of androgen receptor-negative PCa cells via increased matrix metalloproteinase expression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets mainly regulate blood coagulation and hemostasis. The asymmetric status of platelets contributes to cancer promotion and progression, directly causing thrombocytosis in patients with cancer [ 55 ]. Present cell research has already indicated that platelets enhance the invasion of androgen receptor-negative PCa cells via increased matrix metalloproteinase expression [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets mainly regulate blood coagulation and hemostasis. The asymmetric status of platelets contributes to cancer promotion and progression, directly causing thrombocytosis in patients with cancer [55].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the CIBERSORT algorithm was used to calculate the scores of 22 different human immune cell types for each PCa sample ( Hao et al, 2019 ). We used single-sample Gene Set Enrichment Analysis (ssGSEA) to explore the levels of immune cell infiltration ( Hwang et al, 2021 ). DEG identification and functional annotation of DEGs with the “limma” package in R, DEGs were discovered with a p -value of 0.…”
Section: Methodsmentioning
confidence: 99%
“…[ 49 ] Podoplanin is a cell-surface mucin-like glycoprotein that is overexpressed in several tumor cells, as well as in the tumor stroma, inducing platelet aggregation by binding to platelet receptor C-type lectin-like receptor 2 and modulating signal transductions that enhance malignant progression. [ 50 , 51 ] Furthermore, aberrant expression of the podoplanin gene in promyelocytes is the most distinctive transcript of promyelocytic leukemia, and is associated with thrombocytopenia and prolonged bleeding time in a xenograft model. [ 52 ] In preclinical models, platelets binding to CD97 overexpressed on tumor cells can autonomously initiate αIIbβ3-dependent platelet activation to release ATP and LPA, and stimulate tumor cell CD97/LPA receptor-dependent Rho activation, resulting in endothelial junction destruction, vascular extravasation and metastasis.…”
Section: Platelets and Their Rnas Interact With Cancer Cellsmentioning
confidence: 99%